2015
DOI: 10.1016/j.ygcen.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Structural libraries of protein models for multiple species to understand evolution of the renin-angiotensin system

Abstract: The details of protein pathways at a structural level provides a bridge between genetics/molecular biology and physiology. The renin-angiotensin system is involved in many physiological pathways with informative structural details in multiple components. Few studies have been performed assessing structural knowledge across the system. This assessment allows use of bioinformatics tools to fill in missing structural voids. In this paper we detail known structures of the renin-angiotensin system and use computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…The Ace inhibitor enalapril, used to treat patients with high blood pressure, causes intraocular blood vessels to dilate in zebrafish (Kitambi et al, 2009) as expected from conserved functions. The fact that several different Ace inhibitors have similar effects in humans and zebrafish supports both the physiological conservation of the Ace (Prokop et al, 2015).…”
Section: Zebrafish Orthologs and Co-orthologs Of Human Raas Componentmentioning
confidence: 64%
“…The Ace inhibitor enalapril, used to treat patients with high blood pressure, causes intraocular blood vessels to dilate in zebrafish (Kitambi et al, 2009) as expected from conserved functions. The fact that several different Ace inhibitors have similar effects in humans and zebrafish supports both the physiological conservation of the Ace (Prokop et al, 2015).…”
Section: Zebrafish Orthologs and Co-orthologs Of Human Raas Componentmentioning
confidence: 64%
“…The Ace inhibitor blood pressure medication enalapril causes intraocular blood vessels to dilate in zebrafish ( Kitambi et al, 2009 ) as expected from conserved functions. The fact that Ace inhibitors have similar effects in humans and zebrafish supports physiological conservation of the Ace system ( Prokop et al, 2015 ).…”
Section: Discussionmentioning
confidence: 84%
“…The biophysical and structural evidence suggested that SARS-CoV-2 may bind ACE2 with a much higher affinity than SARS-CoV (Wrapp et al, 2020). Our group had previously investigated the evolution of ACE2 throughout species including mapping variants within rat populations (Prokop et al, 2015), a model system for studying the Renin-Angiotensin Aldosterone system (known as the RAAS). We have expanded those tools here, generating ACE2 models for 235 species from mammals to birds/fish, where each of the models are energy minimized with the S protein interaction.…”
Section: Discussionmentioning
confidence: 99%